Synthesis of a selective HDAC6 inhibitor active in neuroblasts. Issue 20 (15th October 2016) - Zwick, Vincent; Simões-Pires, Claudia A.; Nurisso, Alessandra; Petit, Charlotte; Dos Santos Passos, Carolina; Randazzo, Giuseppe Marco; Martinet, Nadine; Bertrand, Philippe; Cuendet, Muriel
Graphical abstract: Abstract: In recent years, the role of HDAC6 in neurodegeneration has been partially elucidated, which led some authors to propose HDAC6 inhibitors as a therapeutic strategy to treat neurodegenerative diseases. In an effort to develop a selective HDAC6 inhibitor which can cross the blood brain barrier (BBB), a modified hydroxamate derivative (compound3 ) was designed and synthetized. This compound was predicted to have potential for BBB penetration based on in silico and in vitro evaluation of passive permeability. When tested for its HDAC inhibitory activity, the IC50 value of compound3 towards HDAC6 was in the nM range in both enzymatic and cell-based assays. Compound3 showed a cell-based selectivity profile close to that of tubastatin A in SH-SY5Y human neuroblastoma cells, and a good BBB permeability profile.